Pengaruh Penggunaan Alat Peraga ROMA “Rompi Mamae” Terhadap Keterampilan Sadari dalam Mencegah Kanker Payudara pada Kader Kesehatan - Rahayu, Dini Dwi; Nur Cory'ah, Fitra Arsy; Gumilang Pratiwi, Intan (Indonesian Health Issue, 2025)
Background: Breast cancer remains a significant global health concern. According to the World Health Organization (WHO), by 2050, the number of new breast cancer cases is projected to increase by 38%, with a 68% rise in mortality, reaching an estimated 3.2 million new cases and 1.1 million deaths annually. In Indonesia, breast cancer is the most common type of cancer, with an incidence rate of 40.3 per 100,000 women and a mortality rate of 16.6 per 100,000 women. Alarmingly, approximately 70% of cases are diagnosed at an advanced stage due to low awareness of early detection. Data show that 90% of Indonesian women have never performed breast self-examination (BSE). This situation is exacerbated in regions such as Lenek Lauq Village, East Lombok Regency, where many health cadres lack sufficient skills in performing BSE. To address this issue, an innovative educational tool called "Rompi Mamae" (ROMA) was developed. Purpose: This study aimed to determine the effect of using ROMA on improving BSE skills among community health cadres. Methods: A quasi-experimental design with a nonequivalent control group design was employed. A total of 48 health cadres were selected and divided into two groups: an intervention group (trained using ROMA) and a control group (provided with standard leaflets). Results: The findings revealed a significant improvement in BSE skills in the intervention group, with a mean post-test score of 31.65 compared to 17.35 in the control group (p = 0.000). Conclusion: ROMA has proven to be an effective and innovative educational medium for enhancing BSE skills among health cadres, with the potential to support broader efforts in early breast cancer detection within the community.